Facile Synthesis, Characterization, and Cytotoxic Activity of Europium-Doped Nanohydroxyapatite - Paulina-Guadalupe Miranda-Meléndez; Gabriel-Alejandro Martínez-Castañón; Nereyda Niño-Martínez; Nuria Patiño-Marín; Miguel-Ángel Casillas-Santana; Brenda-Erendida Castillo-Silva; Facundo Ruiz (Bioinorganic Chemistry and Applications)
The objective of this study was to synthetize europium-doped nanohydroxyapatite using a simple aqueous precipitation method and, thereafter, characterize and impregnate selected samples with 5-fluorouracil in order to explore the properties and the releasing capacity of this material. The nanohydroxyapatite was doped with 3, 5, 10, and 20 wt% of europium. The obtained samples were characterized after they were dried at 80°C and hydrothermal treated at 120°C by 2 hours. The samples were analyzed by transmission electron microscopy, X-ray diffraction analysis, Fourier transform infrared spectroscopy, and photoluminescence. Also, impregnation and release of 5-fluorouracil were assessed in PBS. The toxicity effects of all samples were studied using viability assays on human fibroblasts cells (HGF-1) in vitro. The sizes of the crystallites were about 10–70 nm with irregular morphology and present the phase corresponding to the JCPDS card 9–0432 for hydroxyapatite. The results of the toxicity experiments indicated that doped and undoped powders are biocompatible with fibroblasts cells. Hydroxyapatite samples doped with 5% of europium and loaded with 5-fluorouracil release almost 7 mg/L of the drug after 60 minutes in PBS and decrease the viability of HeLa cells after 24 hours.